MAIN TENSIONS IN THE SOIL UNDER TRACTOR WHEELS - Solarov, O; Perepichay, S (Bulletin of Sumy National Agrarian University. The series: Mechanization and Automation of Production Processes)
The article proposes a method of determining the patterns of a distribution of stresses and strains in the array. It allows to determine the depth and degree of compaction of a particular type of technology and to make rational selection of it for specific conditions. Also, the data obtained in the article make it possible to select the right equipment for tillage.